1969
DOI: 10.1051/rnd:19690310
|View full text |Cite
|
Sign up to set email alerts
|

l'HUILE De Colza Riche en Acide Érucique Et l'HUILE De Colza Sans Acide Érucique. Ii. — Utilisation Digestive Comparée Chez Le Rat

Abstract: dite sans acide érucique produite au Canada à partir de variétés sélectionnées présente, par rapport à l'huile de colza riche en acide érucique, une composition en acides gras profondément modifiée. Les acides érucique (C ' 21) ,) et gadoléique (C 20;¡) sont remplacés par l'acide oléique (6 0 p. 100 des acides gras totaux). Les teneurs en acides gras saturés (6 p. 100 environ) et polymsaturés ne sont p 7L r contre que peu affectées. Cette modification de la composition en acides gras de l'huile entraîne, chez … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
5

Year Published

1972
1972
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
3
10
0
5
Order By: Relevance
“…As the erucic acid (C 22:1) content of the faecal fat is higher than that of the dietary fat, it can be concluded that the erucic acid fraction of RSO is especially poorly digested. This was also shown by Rocquelin and Leclerc [21],…”
Section: Digestibility (A)supporting
confidence: 62%
See 1 more Smart Citation
“…As the erucic acid (C 22:1) content of the faecal fat is higher than that of the dietary fat, it can be concluded that the erucic acid fraction of RSO is especially poorly digested. This was also shown by Rocquelin and Leclerc [21],…”
Section: Digestibility (A)supporting
confidence: 62%
“…This difference can largely be ascribed to the decrease in food intake induced by RSO [15,28], However, in paired feeding experiments in which control animals were allowed to eat as much as animals offered an R SO-containing diet, the con trols still grew more than the RSO-fed animals [22,32], This was explained [32] by the well-documented poorer digestibility of the rapeseed oil [21,29]; however it has never been investigated to see if the poorer digestion of RSO was compensated for by a better digestion of other dietary components.…”
Section: Introductionmentioning
confidence: 99%
“…Ces raisons ont conduit récemment plusieurs auteurs à s'intéresser de nouveau à la composition et à la structure glycéridique de l'huile d'arachide (Kritchevsky et al, 1973 ;Hokes et Worthington, 1979 ;Sanders, 1979 ;Van Pee et al, 1979 ;Manganaro et al, 1981 ;Semporé et Bézard, 1982 (Bugaut et Bézard, 1973 (Rocquelin et Leclerc, 1969 ;Sergiel et Gabucci, 1980 (Clément et Bézard, 1961 (Semporé et Bézard, 1977 ;Bézard et al, 1981 ; Sawadogo et Bézard, 1977). Les (Bézard et al, 1981 ;Semporé et Bézard, 1982 ; Sawadogo et Bézard, 1982 b (Litchfield, 1972 (Bézard et al, 1981).…”
unclassified
“…Les (Bézard et al, 1981 ;Semporé et Bézard, 1982 ; Sawadogo et Bézard, 1982 b (Litchfield, 1972 (Bézard et al, 1981). Le pourcentage de ces fractions est celui calculé à partir de la composition des monoacylglycérols (Bézard et al, 1981 ;Semporé et Bézard, 1982 (Litchfield, 1972 (Rocquelin et Leclerc, 1969 (Semporé et .…”
unclassified
“…Un certain nombre de travaux ont déjà été publiés ces dix dernières années sur l'utilisation digestive de l'acide érucique ou cis n-9 docosénoïque (C 22 : 1) chez le Rat (Rocquelin et Leclerc, 1969 ;Rocquelin et al, 1975 ;Hornstra, 1972 ; . Dans l'ensemble, les résultats obtenus montrent que cet acide gras à très longue chaîne est à l'origine de la médiocre utilisation digestive de certaines huiles de colza qui en contiennent jusqu'à 50 p. 100 des acides gras totaux.…”
unclassified